INFLUENCE OF REGIONAL LYMPHOTROPIC ANTIBACTERIAL THERAPY ON THE PROGRESSION OF PHLEGMONS IN THE MAXILLOFACIAL REGION - Malanchuk, V.O.; Sidoryako, A.V.; Sidoryako, S.V. (World of Medicine and Biology, 2020)
The lymphatic system is a part of human circulatory system and is actively involved in providing the body’s immune response. It repeats the vasculature, consisting of lymphatic capillaries, vessels, as well as evenly distributed lymphoid tissue, which is part of the lymph nodes and aggregate glands of the small intestine (Peyer’s patches) and others. 100 patients with acute odontogenic inflammatory diseases of the maxillofacial region were examined. Patients received traditional drug treatment. In addition, we included regional lymphotropic antibacterial therapy to the main method of treatment. Regional lymphotropic administration of antibacterial drug in the treatment of phlegmons of the maxillofacial region leads to an accelerated onset of the second phase of the wound process development, more rapid detoxification of the body, a decrease in the number of complications, as well as the prevalence of pronounced positive lymphogram dynamics.